A Revision Of Scientific Research Ä°n Jordanian Higher Education Institutions: A Follow-Up Assessment - Tareef, Atif bin; Alzyood, Mohammad S. (European Scientific Journal, ESJ, 2016)
This study aimed at identifying the status and obstacles of scientific research in Jordanian higher education institutions as perceived by vice presidents, deans and vice deans of the scientific research departments. In addition to differences in status and obstacles, pursuant to the study variable, this is the institution type.The sample composed of (139) faculty members and all 27 vice presidents, deans and vice deans of the scientific research departments at all 27 Jordanian universities.Having reviewed all interviews and some literature, the researcher prepared a questionnaire, which was tested for validity and reliability of the questionnaire, and used five-likert scale to measure the status and the obstacles of the scientific research in higher education in Jordan. The study showed the following findings; The scientific research status mean was 2.19 and that was low result, also the themes have almost the same results where the research planning got the highest among the themes and the research support the lowest. The scientific research obstacles mean was 2.87 and that was low result, also the themes have almost the same results while doing research for academic promotion got the highest among the themes and doing research for developing human knowledge and enjoyment the lowest. In the light of these results, the study provides a number of recommendations that could reduce the obstacles for funding of scientific research in higher education.